HIKAYAT PERANG SABIL DI LAYAR TIKTOK: REPRODUKSI NARASI HEROISME ACEH MASA KINI - Mustaqim Mustaqim (Yayasan An-Nur Meunara Baro, 2025)
This article investigates how the narrative of heroism in Hikayat Perang Sabil is digitally reproduced on TikTok by Aceh’s younger generation. The shift from ancient manuscripts to short-form video content creates a new landscape for transmitting historical values. Employing a digital ethnographic approach, the study observes over 100 TikTok videos tagged #PerangSabil across six months, complemented by in-depth interviews with content creators and young users, and semiotic analysis of visual, audio, and symbolic elements. Findings reveal that themes of jihad and struggle are repackaged using popular visual language and viral strategies, such as traditional music remixes, cinematic dramatization, and emotionally charged texts. TikTok serves as a cultural negotiation space between traditional values and contemporary digital expression. While there is appreciation for the preservation of collective memory, criticisms arise concerning the oversimplification of historical meanings. The study concludes that digital platforms, despite their limitations, hold significant potential for shaping a dynamic and inclusive historical consciousness, but require historical literacy and ethical collaborations between historians and content creators.